2019
DOI: 10.1186/s12284-019-0310-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new rice cultivars and resistance loci against rice black-streaked dwarf virus disease through genome-wide association study

Abstract: Background The rice black-streaked dwarf virus (RBSDV) disease causes severe rice yield losses in Eastern China and other East Asian countries. Breeding resistant cultivars is the most economical and effective strategy to control the disease. However, few varieties and QTLs for RBSDV resistance have been identified to date. Results In this study, we conducted a genome-wide association study (GWAS) on RBSDV resistance using the rice diversity panel 1 (RDP1) cultivars tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Although commercial varieties lack resistance to RBSDV, several resistance sources have been identified in the germplasm of diverse cultivars of rice and maize and related species (Luan et al, 2012;Hajano et al, 2016;Feng et al, 2019). These studies revealed a low percentage of resistant lines and no immune or highly resistant materials among the temperate sources of japonica germplasm, but several aus-type, indica, and tropical japonica subspecies have high levels of resistance, which have been reported to be controlled by quantitative trait loci (QTLs) or multiple genes (Wang et al, 2010;Zheng et al, 2012).…”
Section: Is E a S E Manag Ementmentioning
confidence: 99%
See 2 more Smart Citations
“…Although commercial varieties lack resistance to RBSDV, several resistance sources have been identified in the germplasm of diverse cultivars of rice and maize and related species (Luan et al, 2012;Hajano et al, 2016;Feng et al, 2019). These studies revealed a low percentage of resistant lines and no immune or highly resistant materials among the temperate sources of japonica germplasm, but several aus-type, indica, and tropical japonica subspecies have high levels of resistance, which have been reported to be controlled by quantitative trait loci (QTLs) or multiple genes (Wang et al, 2010;Zheng et al, 2012).…”
Section: Is E a S E Manag Ementmentioning
confidence: 99%
“…These studies revealed a low percentage of resistant lines and no immune or highly resistant materials among the temperate sources of japonica germplasm, but several aus-type, indica, and tropical japonica subspecies have high levels of resistance, which have been reported to be controlled by quantitative trait loci (QTLs) or multiple genes (Wang et al, 2010;Zheng et al, 2012). To facilitate the use and transfer of host resistance in breeding programmes, recent QTL mapping or genome-wide association studies have identified genomic regions associated with RBSDV resistance and linked DNA markers (Feng et al, 2019;Xiao et al, 2019). Several QTLs on different chromosomes have been identified in japonica cultivar Koshihikari, and indica cultivars Minghui 63, WR24, Tetep, IR36, and 9194 (Wang et al, 2010;Li et al, 2013;Zhou et al, 2015a;Zhang et al, 2016;Sun et al, 2017;Xu et al, 2018).…”
Section: Is E a S E Manag Ementmentioning
confidence: 99%
See 1 more Smart Citation
“…Breeding resistant cultivars are one of the most economical and effective strategies to control the disease. In the past two decades, there were several studies on the identification of cultivars and the detection of QTLs for RBSDV resistance (Feng et al ., 2019). However, few highly resistant germplasms or genes have been found (Sun et al ., 2017), severely hindering the development of elite varieties with high RBSDV resistance through either conventional breeding or marker‐assisted selection (MAS) breeding.…”
Section: Figurementioning
confidence: 99%
“…Rice black-streaked dwarf virus (RBSDV) is a member in the Genus Fijivirus, family Reoviridae. RBSDV is known to be transmitted by small brown planthopper (SBPH, Laodelphax striatellus) in a persistent manner (Shikata and Kitagawa 1977;Hibino 1996;Feng et al 2019), and can cause severe damages to rice (Oryza sativa), maize (Zea mays), and several other cereal crops in the eastern region of Asia. RBSDV symptoms in rice plants include plant stunting, leaf dark greening, pale green enation formation, and dark color leaf vein swellings (Bai et al 2002;Chen and Zhang 2005;Lee et al 2005).…”
Section: Introductionmentioning
confidence: 99%